PERNIKAHAN DINI DALAM TINJAUAN UNDANG-UNDANG DAN PSIKOLOGI - Ahmad Khoiri (Universitas Islam Lamongan, 2018)
Abstract: The problem of early marriage is always interesting to discuss and debate for being capable of raising the pros and cons. Various responses to early marriage appeared both positively and negatively. Early marriage is a social phenomenon that occurs in many parts of the world with different backgrounds. This is certainly a concern for the international community, given the risks arising from early marriage are physically and psychologically, including sexual relations. Poverty is not the only important factor that plays a role in early marriage. When we trace the roots of the problem of early marriage in Indonesia, especially on the island of Java it has actually become something commonplace for our ancestors. In their context there is a negative stigma if a woman marries at an adult age in their community. This paper will discuss the phenomenon of early marriage in the context of law and psychology. To some extent those who have an early marriage will experience psychological risks such as stress, irritability, anxiety and depression.Keywords: Early marriage, Islamic Law, psychology